Development of Anagram Flash Cards to Stimulate Early Literacy in Children Aged 5–6 Years - Khusnul Mariyyah Supriadi; Winda Sherly Utami; Sri Indriani Harianja (Darul Yasin Al Sys, 2026)
This study addresses the problem of low early literacy skills among children aged 5–6 years in early childhood education units in Suka Karya Village, Jambi City, and aims to develop anagram flash card media to stimulate early literacy skills, including recognition of letters a–z, initial letters, and emergent writing. Using the ADDIE development model, limited to the teacher practicality test stage (analysis, design, development, and implementation), data were collected through teacher interviews, expert validation, and teacher response questionnaires. The results show that the developed anagram flash card media are considered very feasible, practical, and effective in supporting early literacy learning for children aged 5–6 years, as evidenced by material and media expert validation scores that increased at each assessment stage. In material validation, expert validator 1 rated the media at 80.56% and 88.89% (both very feasible), while expert validator 2’s ratings increased from 63.83% (feasible) to 77.78% and 94.44% (both very feasible). In media validation, expert validator 1’s assessment rose from 91.67% to 100%, and expert validator 2’s ratings moved from 95% to 90% and then 98.33%, all within the very feasible category. Teacher responses further indicated very high practicality, with a feasibility rating of 91.67%. These findings indicate that the anagram flash card media underwent significant improvement throughout the development process and are highly suitable for classroom use, contributing to the enhancement of children’s early literacy skills and underscoring the importance of innovative, multisensory media tailored to developmental stages in early childhood education. Future research is recommended to apply this media to larger samples and conduct direct classroom trials to strengthen empirical evidence of its effectiveness.